2015
DOI: 10.1021/acssuschemeng.5b00226
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Leather Using Deep Eutectic Solvents

Abstract: Processing of leather has an historical reputation as a chemically and energetically intensive process which produces large volumes of aqueous waste. Saline pollution combined with heavy-metal, dyes and acid and base streams make leather production an ecologically sensitive industry. The current study shows that a variety of deep eutectic solvents, DESs may be used for the tanning, fatliquoring and dyeing of animal hides, being particularly useful for mineral (chromium) and vegetable tanning processes. The tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The partition coefficients between decane and 1 ChCl: 2 EG are shown in Table 5. It can be seen from High solubilities have previously been observed for large molecules such as lignin [27] and vegetable tans [28] in DESs. This presumably because of the large enthalpy of solvation resulting from the solute having a large number of hydroxyl functional groups.…”
Section: Effect Of Solute Hydrogen Bondingmentioning
confidence: 80%
“…The partition coefficients between decane and 1 ChCl: 2 EG are shown in Table 5. It can be seen from High solubilities have previously been observed for large molecules such as lignin [27] and vegetable tans [28] in DESs. This presumably because of the large enthalpy of solvation resulting from the solute having a large number of hydroxyl functional groups.…”
Section: Effect Of Solute Hydrogen Bondingmentioning
confidence: 80%
“…Results show that initially, the IL monomers interact with gelatin at the interface but at higher concentrations hydrophobic micro domains were observed. A study by Alaysuy investigated the effect of DESs on collagen in leather [30]. Results showed that the DES did not denature the collagen structure but was absorbed into the macroscopic pores and could be forced out of the structure with applied pressure, i.e., the DES did not change the crystalline structure of the collagen.…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated as a useful option for both chrome and vegetable tanning [61,62]. However, the more exciting aspect is the possibility of using chemistries currently not possible, for example introducing graphite deep into the collagen structure.…”
Section: Reagent Deliverymentioning
confidence: 99%